Pengembangan Multimedia Batik Khas Purworejo untuk Meningkatkan Aspek Psikomotorik Halus pada Mata Pelajaran Seni Budaya dan Prakarya - Rizaldi Nurmawan; Muflikhul Khaq; Titi Anjarini (Jurnal Kualita Pendidikan, 2021)
This study aims to: 1) the feasibility of multimedia learning media typical of Purworejo batik in improving psychomotor aspects based on material and media experts, 2) how the development of learning media typical of Purworejo batik can improve subtle psychomotor, 3) how students respond to the use of multimedia learning media. This research is a research and development (R & D)). Research development refers to the Borg & Gall model with 10 stages of development. The platform used by kahoot.com. The object of this research is the interactive multimedia learning model of Purworejo batik. The research subjects were fourth grade students. The results showed that: 1) The multimedia learning media with the Kahoot application used in Purworejo batik material at SD N Purworejo was declared feasible to be developed from an assessment by media experts because it had a value of 90 when viewed from the programming aspect, it got a score of 86.6 seen from the display aspect. media. Based on material experts, it has a value of 83.3 in the first trial and 94.4 in the second trial. 2) Multimedia learning media with the Kahoot application, can stimulate students' fine psychomotor skills when used in Purworejo batik material at SD N Purworejo. This can be seen from the results of the pretest showing a score of 59%, after learning with the Kahoot application has increased to 90%. 3) Multimedia learning media with the Kahoot application, got a good response from students because of the 28 respondents all gave good and very good ratings.